Pros and Cons of Implementing Mudharabah Agreement for Agricultural Financing with the Implementation of Maqosid Sharia (Case Study of the Implementation of the Mudhorobah Agricultural Agreement in Tamzis KPPS) - muhamad saifidin (Sekolah Tinggi Ekonomi dan Bisnis Islam Lampung, 2020)
This study wants to find out how efficient the use of contracts in financing is in Islamic financial institutions, especially agricultural financing. This study also wants to look at the efficiency and repositioning of the use of mudharabah contracts in agricultural financing, which is seen by the efficiency of institutions and financing members. This research is applied research that is research conducted by an Islamic financial institution KPPS Tamzis Bina Utama. This research method uses leprosy and interview methods. The results of this study prove that the use of the contract basically is based on the value of the error that will be achieved in terms of both the prodak provider and prodak user.